A Change in the Frame: From Absenteeism to Attendance - Gentle-Genitty, Carolyn; Taylor, James; Renguette, Corinne (Frontiers in Education, 2020)
School attendance is important for student long-term academic and career success. However, in the U.S., our current practice often disenfranchises more at-risk students than it helps. Students slated for suspension and expulsion are often recipients of these practices. This manuscript offers a recommended change in how we frame student absenteeism and attendance using attendance markers and conceptual information by identifying the discrepancies, proposing options, and recommending a new way to actively leverage attendance data (not absenteeism data) for proactive student support. Particular attention is paid to how excused and unexcused absences and in-school suspensions are treated. An emerging pivot program, the Evaluation and Support Program, engages students while they receive school services, community support, and complete consequences is discussed as a possible, promising intervention.